The Effectiveness of Gamification in FitHub Yogyakarta's CRM to Increase Customer Participation and Retention - Aisyah Nasution; Muhammad Thoyib Amali (Interdisciplinary Social Studies, 2025)
The digital fitness industry is growing with the adoption of technology that encourages gyms to optimize Customer Relationship Management (CRM). One of the innovative strategies used is gamification, which is the application of game elements such as points, badges, leaderboards, challenges, and streaks in customer interaction. This study examines the effectiveness of gamification in FitHub Yogyakarta's CRM to increase customer participation and retention. The theoretical foundations used are Self-Determination Theory (SDT), which emphasizes basic psychological needs, and the Stimulus–Organism–Response (S-O-R) model, which describes the psychological process from gamification stimulus to response in the form of involvement. Previous empirical evidence suggests gamification is effective in increasing engagement, loyalty, and physical activity behavior. However, research in the context of Indonesian fitness centers is still limited. Therefore, this study contributes theoretically to the development of gamification literature and the practicality of providing gamification-based strategies for gym managers.